Vending machine service: relationship between service quality and student's satisfaction - Bagah, Casey Brent; Ag Jaffar, Fareezal; Omar, Latipah; Abu Bakar, Noor Ain; Lojingki, Terry (2014)
Technology has brought conveniences in various industries especially in the retail business. As for the self-service technologies, providing a good service to the customer is important as it would increase customers' satisfaction. However, the factors influencing customers' satisfaction when engaging with self-service technologies, vending machine, have yet to be identified, especially among the UiTM Sabah's students. Based on the previous study, there are seven dimensions that affect customers' decision to use vending machine which include functionality, enjoyment, security/privacy, assurance, design, convenience, and customization. The study mainly discuss on design, security/privacy, assurance and functionality which leaves the other remaining factors unclear of its existence. The three factors enjoyment, customization and convenience are selected as potential factors of service quality in determining the effect it has on customers' satisfaction. Therefore, this research aims to identify the components of service quality and its relationship with students satisfactory on the vending machine service. In the meantime, the relationship of service quality and students satisfactory will also be studied.